Inside Back Cover: Recent progress in low‐cost noncovalently fused‐ring electron acceptors for organic solar cells. Issue 6 (26th December 2022) - Bai, Qingqing; Liang, Qiming; Li, Henan; Sun, Huiliang; Guo, Xugang
Abstract : Toward future commercial applications of organic solar cells (OSCs), organic photovoltaic materials that enable high efficiency, stability, and low cost should be developed. In article number e281, Sun and co‐workers comprehensively summarize works about noncovalently fused‐ring electron acceptors with low‐cost and good stability from molecular design, efficiency optimization to material cost analysis.